2007
DOI: 10.1016/j.febslet.2007.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stability of cis Pro‐Pro peptide bond in Pro‐Pro‐Phe sequence motif

Abstract: Identification of sequence motifs that favor cis peptide bonds in proteins is important for understanding and designing proteins containing turns mediated by cis peptide conformations. From 1 H NMR solution studies on short peptides, we show that the Pro-Pro peptide bond in Pro-Pro-Phe almost equally populates the cis and trans isomers, with the cis isomer stabilized by a CHÁ Á Áp interaction involving the terminal Pro and Phe. We also show that Phe is over-represented at sequence positions immediately followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 27 publications
4
49
1
Order By: Relevance
“…1,68,20 Studies by Creighton and Basu indicated that cis-Pro-Aromatic interactions, primarily with H α ( i −2) of Gly or Pro two residues prior to Tyr/Trp/Phe, are enthalpically favorable and dependent on electronics of the aromatic residue. 10,11,20,22,23 Aromatic-Pro-aromatic sequences also exhibit a high propensity for cis amide bonds, with aromatic rings able to stack against both faces of the proline ring. 8 Interestingly, Dyson and Wright found that in SYPXDV peptides, the highest population of cis amide bonds was observed with Phe, rather than Tyr or Trp, at the X position.…”
Section: Local Aromatic-proline Interactionsmentioning
confidence: 99%
“…1,68,20 Studies by Creighton and Basu indicated that cis-Pro-Aromatic interactions, primarily with H α ( i −2) of Gly or Pro two residues prior to Tyr/Trp/Phe, are enthalpically favorable and dependent on electronics of the aromatic residue. 10,11,20,22,23 Aromatic-Pro-aromatic sequences also exhibit a high propensity for cis amide bonds, with aromatic rings able to stack against both faces of the proline ring. 8 Interestingly, Dyson and Wright found that in SYPXDV peptides, the highest population of cis amide bonds was observed with Phe, rather than Tyr or Trp, at the X position.…”
Section: Local Aromatic-proline Interactionsmentioning
confidence: 99%
“…Moreover, the four cis-trans states also gave rise to multiple spin systems for the aliphatic protons of the proline residues. Although the peaks' assignment result was intricate, we could observe a proline Hα proton highly upfielded (3.77 ppm), likely due to the close proximity of the P3-F5 side chains, as found in some proteins and peptide containing the segment P-P-F, 12 which gives rise to the ring current effect on Hα protons of the first proline. Closely interacting P3-F5 side chains are supposed to be at the basis of the observed stability of the proline-proline cis conformers in the segment P-P-F, when present in a short peptide, devoid of any tertiary interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, besides the consensus sequence Pro-Phe (P-F) present in common PPIase substrates, a second P was inserted before the P-F segment, as suggested by several other studies. 12 Moreover, a lysine (K6 in PP peptide or K8 in EPP peptide) was introduced in both sequences to improve the peptide solubility. A glutamic acid was inserted at the N-terminus of the EPP peptide (E1) to potentially stabilize the cis conformation of the X-Pro bond through a salt bridge with the K8 at the C-terminus.…”
Section: Resultsmentioning
confidence: 99%
“…The population of the cis-conformation was estimated to be 16.3% (from Phe beta protons; see inset to Figure 4A) and 17.2% (from Pro delta protons; data not shown). The two 3 J ab values for Phe were nonidentical (5.8 and 10.1 Hz) in the cis-Pro conformation (inset to Figure 4A) indicating restricted ring rotation, [21][22][23] as opposed to similar values of 3 J ab for the trans-Pro conformation (7.0 and 8.0 Hz) indicating free rotation of the Phe side chain.…”
Section: Nmr Studies On Designed Peptides With [Glu/gln]-pro-aro-xamentioning
confidence: 96%
“…Previous NMR studies from our laboratory, performed on a series of three‐residue peptides with the general sequence Xaa‐Pro‐Tyr showed that the cis Pro conformation is stabilized in the motif through CH ⋅⋅⋅ π interaction when Xaa = Ala, Gly, Pro, Tyr, Phe and Trp. Although the experimental result correlated well with trends observed in protein structural database, Xaa = Glu was an exception.…”
Section: Introductionmentioning
confidence: 98%